Development and preliminary validation of five miRNAs for lung adenocarcinoma prognostic model associated with immune infiltration - Huanzhang Yang; Jingli Hua; Yanxia Han; Dong Chang; Wenlong Zheng (Scientific Reports)
Abstract Our aim was to investigate the potential value of immune-related miRNA signaling in predicting clinical prognosis and immunotherapy. We first identified immune-related miRNAs in lung adenocarcinoma (LUAD), and then constructed a miRNA-based risk model by lasso regression modeling. Finally, we validated our findings using RT-qPCR in serum from LUAD patients and normal patients. Weighted gene co-expression network analysis (WGCNA) was used to screen the aberrantly expressed genes associated with immune scores, and then correlation analysis and prognostic analysis were used to identify and immune-associated miRNAs, and lasso-cox regression was used to construct an immune-associated 5-miRNA model. Risk score as an independent prognostic factor could accurately predict the prognosis of LUAD patients. Immunotherapy analysis revealed that patients with low-risk scores benefited more from anti-PD-1 and CTLA-4 therapy. Experimental validation showed that only miRNA-200b-3p was significantly differentially expressed in 91 cases of clinically collected cancer tissues and normal tissue serum. We constructed a 5-miRNA model that can be used for risk stratification of LUAD patients. Targeted therapy against miRNA-200b-3p is expected to be a prospective new strategy for the clinical treatment of LUAD.